1996
DOI: 10.1128/jvi.70.5.3298-3301.1996
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the serological relatedness of genital human papillomaviruses by hemagglutination inhibition

Abstract: To assess the potential for cross-protection among genital human papillomavirus (HPV) types in virus-like particle (VLP)-based vaccinations, inhibition of HPV VLP-mediated hemagglutination by rabbit antisera raised against HPV type 6b (HPV-6b), HPV-11, HPV-16, HPV-18, HPV-31, HPV-33, and HPV-45 was analyzed. Only highly homologous types (HPV-6b and HPV-11, and HPV-18 and HPV-45) exhibited detectable serological cross-reaction for the class of antibodies that inhibit virion-to-cell surface binding. However, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
1
5

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(80 citation statements)
references
References 29 publications
4
70
1
5
Order By: Relevance
“…Antibody responses to VLP vaccination are mainly type-restricted, yet cross-neutralising immune responses have been observed that confer partial cross-protection to closely related HPV types in human vaccine trials (Roden et al 1996;Pastrana et al 2005;Villa et al 2005). BPV-1 and BPV-2 are closely related genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody responses to VLP vaccination are mainly type-restricted, yet cross-neutralising immune responses have been observed that confer partial cross-protection to closely related HPV types in human vaccine trials (Roden et al 1996;Pastrana et al 2005;Villa et al 2005). BPV-1 and BPV-2 are closely related genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Populations at high risk for cervical cancer, and populations with high rates of human immunodeficiency virus (HIV) infection, tend to show higher proportions of infections with multiple types, as compared with populations that do not belong to these risk groups [4]. Epidemiological studies suggest that the immune response to HPV is type-specific [5], but there is no agreement concerning the influence of infection with multiple HPV types on cervical carcinogenesis. According to Trottier et al [6], infections with multiple HPV types seem to act synergically in cervical carcinogenesis.…”
mentioning
confidence: 99%
“…Antibodies from 44.0% of patients inhibited HPV16 VLP-induced hemagglutination, suggesting that they recognize conformational epitopes on the capsid proteins. Hemagglutination inhibition assay has been regarded as a surrogate method to evaluate the neutralization potential of antibodies [11]. As far as we are aware this is the ¢rst report of the use of such methodology for the study of human secretory antibodies to HPV16.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all of them are suit-able for the study of large numbers of human samples. Inhibition of HPV virus-like particles (VLP)-induced hemagglutination of mouse red blood cells (RBCs) has been used as a surrogate assay to evaluate neutralizing responses [11], and provides a useful methodology for the study of human cervical mucus samples.…”
Section: Introductionmentioning
confidence: 99%